2023
DOI: 10.3389/fpsyg.2023.1051558
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence profiles of professionals in Kuwait

Abstract: Trait emotional intelligence concerns people’s perceptions of their emotional world. Our aims for this study are to examine (a) the trait emotional intelligence (EI) profiles across different professions in Kuwait; (b) the incremental validity of trait EI in predicting job performance; and (c) the relationship between trait EI, job attitudes, and job performance. The sample comprised 314 professionals in Kuwait in seven different professions: Bankers, Engineers, Healthcare providers, Lawyers, Military, Policem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…All TEIQue instruments are available, free of charge, for research purposes from www.psychometriclab.com . In this study, we used the Kuwaiti-Arabic adaptation of TEIQue-SF [ 35 ], which has shown robust psychometric properties in Kuwaiti samples.…”
Section: Methodsmentioning
confidence: 99%
“…All TEIQue instruments are available, free of charge, for research purposes from www.psychometriclab.com . In this study, we used the Kuwaiti-Arabic adaptation of TEIQue-SF [ 35 ], which has shown robust psychometric properties in Kuwaiti samples.…”
Section: Methodsmentioning
confidence: 99%